2016
DOI: 10.1038/srep26723
|View full text |Cite
|
Sign up to set email alerts
|

Identification of lactate dehydrogenase as a mammalian pyrroloquinoline quinone (PQQ)-binding protein

Abstract: Pyrroloquinoline quinone (PQQ), a redox-active o-quinone, is an important nutrient involved in numerous physiological and biochemical processes in mammals. Despite such beneficial functions, the underlying molecular mechanisms remain to be established. In the present study, using PQQ-immobilized Sepharose beads as a probe, we examined the presence of protein(s) that are capable of binding PQQ in mouse NIH/3T3 fibroblasts and identified five cellular proteins, including l-lactate dehydrogenase (LDH) A chain, as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
44
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 54 publications
(67 reference statements)
1
44
0
Order By: Relevance
“…Despite continuous feeding with WD postnatally, early exposure to di‐sodiated PQQ attenuated the development of liver injury and fibrosis through mechanisms that appear to involve restoration of oxidative metabolism in macrophages and retention of an early life microbial composition. In addition to its antioxidant action, PQQ is a noted potentiator of oxidoreductase activity, both in bacteria and mammals, and promotes oxidative metabolism through modulation of lactate dehydrogenase activity . The increased abundance of citrate in BMDMs following stimulation combined with the augmented response in WD‐fed mice with rescue by in vitro addition of PQQ suggests that reprogramming of the TCA cycle at isocitrate dehydrogenase may be attenuated by PQQ.…”
Section: Discussionmentioning
confidence: 99%
“…Despite continuous feeding with WD postnatally, early exposure to di‐sodiated PQQ attenuated the development of liver injury and fibrosis through mechanisms that appear to involve restoration of oxidative metabolism in macrophages and retention of an early life microbial composition. In addition to its antioxidant action, PQQ is a noted potentiator of oxidoreductase activity, both in bacteria and mammals, and promotes oxidative metabolism through modulation of lactate dehydrogenase activity . The increased abundance of citrate in BMDMs following stimulation combined with the augmented response in WD‐fed mice with rescue by in vitro addition of PQQ suggests that reprogramming of the TCA cycle at isocitrate dehydrogenase may be attenuated by PQQ.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in rodents showed that increased centrifugation force would damage the cell organelles and membranes of sperm [10][11][12] . However, few studies have been conducted to further explore the effect of the sperm suffering excess centrifugation force on the outcomes of IVF in any species.…”
Section: Discussionmentioning
confidence: 96%
“…However, few studies have been conducted to further explore the effect of the sperm suffering excess centrifugation force on the outcomes of IVF in any species. Only one study showed that rat sperm with over centrifugation had no impact on the fertilization rate 12 . In line with that, we also found that double centrifugation did not decrease the fertilization rate, nor the other indicators mentioned above.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The loss of γ radiation mediated activation of RqkA in the DpqqE mutant and absence of γ 381 radiation response of RqkA KD autophosphorylation suggest the importance of both WD40 382 domain and PQQ in the activation of RqkA function in response to γ radiation and DNA 383 damage-induced signaling through RqkA. PQQ has recently been shown to physically 384 interact with cellular proteins in the mammalian system and crucial for the regulation of their 385 enzymatic activity(Akagawa et al, 2016). RqkA phosphorylates DNA repair and cell 386 division proteins in response to gamma radiation and DNA damage (Rajpurohit and Misra, 387 2013a,Rajpurohit et al, 2016.…”
mentioning
confidence: 99%